(untitled) (Conference Zone, 2022)
This article outlines the main course of action in Russian foreign policy following the collapse of the Soviet Union in 1991. The article especially focuses on post-Soviet countries and bilateral relations with Russia, applying realist and liberal analyses of Russian struggle for regional hegemony.